2017
DOI: 10.1074/jbc.m117.799296
|View full text |Cite|
|
Sign up to set email alerts
|

Fic-mediated deAMPylation is not dependent on homodimerization and rescues toxic AMPylation in flies

Abstract: Protein chaperones play a critical role in proteostasis. The activity of the major endoplasmic reticulum chaperone BiP (GRP78) is regulated by Fic-mediated AMPylation during resting states. By contrast, during times of stress, BiP is deAMPylated. Here, we show that excessive AMPylation by a constitutively active Fic E247G mutant is lethal in Drosophila. This lethality is cell-autonomous, as directed expression of the mutant Fic E247G to the fly eye does not kill the fly but rather results in a rough and reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
81
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(92 citation statements)
references
References 29 publications
5
81
1
5
Order By: Relevance
“…We hypothesize that depending on specific cellular signals, the rate of adenylylation versus de-AMPylation reaction differs, leading to elevated levels of either adenylylated or de-AMPylated BiP. Indeed, it was recently reported that while the HYPE dimer functions primarily as an adenylytransferase, HYPE in its monomeric form functions as a de-AMPylase (30). This finding supports our data showing de-AMPylation of BiP and HYPE by WT-HYPE even in the presence of an equal concentration of E234G-HYPE.…”
Section: Kinetic Parameters For the De-ampylation Of Bipmentioning
confidence: 99%
“…We hypothesize that depending on specific cellular signals, the rate of adenylylation versus de-AMPylation reaction differs, leading to elevated levels of either adenylylated or de-AMPylated BiP. Indeed, it was recently reported that while the HYPE dimer functions primarily as an adenylytransferase, HYPE in its monomeric form functions as a de-AMPylase (30). This finding supports our data showing de-AMPylation of BiP and HYPE by WT-HYPE even in the presence of an equal concentration of E234G-HYPE.…”
Section: Kinetic Parameters For the De-ampylation Of Bipmentioning
confidence: 99%
“…In contrast, a BiP transgene mutated at a second reported AMPylation site (Casey et 97 al., 2017;Preissler et al, 2015), BiP T518A , did not rescue BiP -/lethality. As fic null mutants that 98 lack BiP AMPylation are viable, the lethality of the BiP T518A mutant is not likely to be due to the 99 loss of AMPylation (Casey et al, 2017). Instead, these observations indicate an essential role for 100…”
mentioning
confidence: 91%
“…Previously, we reported that over-expression of the constitutively active AMPylating 104 Fic E247G was lethal in a fic-null fly background (fic 30C ) because it lacks the essential 105 deAMPylation activity (Casey et al, 2017). We tested whether flies expressing the AMPylation-106 resistant BiP T366A could survive this lethality.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Recent data show that FICD regulates the ATPase activity of HSPA5 and its interactions with unfolded proteins, but the exact function is not yet clear 13 . However, it was found that the HSPA5 AMPylation associates with changes in neuronal fitness in drosophila 3, [14][15][16] .…”
mentioning
confidence: 99%